ANALISIS MUTU DAN EKONOMI PENERAPAN PENGEMASAN VAKUM BAWANG DAUN POTONGAN (Allium fistulosum L.) SELAMA PENYIMPANAN - Mikael, Florensi Wahyuni; Molenaar, Robert; Lengkey, Lady C. Ch. E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
AbstractThis study aimed to analyze leeks packaging and without packaging during storage, and to analyze economical packaging and knowing the number of breakeven points obtained. This study uses an experimental method, and descriptive analysis of data consisting of 2 treatments and 3 replications, namely scallions which are vacuum packed, and leeks without packaging that are stored in a refrigerator with a temperature of 5-10˚C.From the results of research on quality analysis of changes in weight, color and texture showed that the vacuum packaged onions at a storage temperature of 5˚C – 10˚C gave the best results over a 14-day shelf life compared to unpacked leeks which only lasted for a shelf life of 6 days. Weight reduction occurred in the treatment without packaging by 44%. The total fixed cost is Rp.219,625 /Year, the total variable cost is Rp.5,519 per package, with a yearly production of 24,300 packs /Year, to obtain the selling price of vacuum packaging leeks of Rp.6,080 per package, and the break-even analysis results in get is 392 packaging /Year.Keywords : Leeks, Vacuum Packaging, Storage Time